TikTok and YouTube Content Preferences among Gen Alpha Students: Opportunities and Challenges in Developing Islamic Character at SMPN 5 Jerowaru - Muhammad Yusuf Arfizi (AS-SABIQUN, 2026)
Although social media use among Generation Alpha has received increasing scholarly attention, limited research has examined students’ content preferences across both TikTok and YouTube and their implications for Islamic character formation. This study aimed to explore students’ TikTok and YouTube content preferences, identify the opportunities and challenges of Islamic character formation through these platforms, and analyze teachers’ strategies for addressing the negative impacts of social media at SMPN 5 Jerowaru. A qualitative descriptive design was employed using purposive sampling. Data were collected through observations, semi-structured interviews, and document analysis and were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing. The findings show that TikTok is predominantly used for entertainment, social interaction, and participation in digital trends, whereas YouTube functions as a platform for educational enrichment, information seeking, and religious learning. Students’ content preferences are shaped by generational characteristics, peer interactions, algorithmic recommendations, digital literacy levels, and guidance from teachers and parents. The findings further reveal both opportunities and challenges in Islamic character formation. Educational and religious content supports religious awareness, self-regulation, moral responsibility, and digital ethics; however, entertainment-oriented content, algorithm-driven exposure, limited digital literacy, and insufficient supervision may hinder character development. Teachers address these challenges through value-based digital literacy, mentoring and role-modeling practices, and teacher–parent collaboration. This study concludes that social media influences Islamic character formation through the quality of content consumed and the effectiveness of educational guidance. The findings contribute to digital-era Islamic character education and provide practical implications for promoting responsible, ethical, and value-oriented digital engagement among Generation Alpha students.